2018
DOI: 10.1016/j.immuni.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody Targeting the Fusion Machinery Neutralizes Dual-Tropic Infection and Defines a Site of Vulnerability on Epstein-Barr Virus

Abstract: Epstein-Barr virus (EBV) is a causative agent of infectious mononucleosis and is associated with 200,000 new cases of cancer and 140,000 deaths annually. Subunit vaccines against this pathogen have focused on the gp350 glycoprotein and remain unsuccessful. We isolated human antibodies recognizing the EBV fusion machinery (gH/gL and gB) from rare memory B cells. One anti-gH/gL antibody, AMMO1, potently neutralized infection of B cells and epithelial cells, the two major cell types targeted by EBV. We determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
187
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(194 citation statements)
references
References 100 publications
(170 reference statements)
7
187
0
Order By: Relevance
“…We are grateful to Thomas Hinds and Ning Zheng for assistance with the crystallization robot and BLI device; to Jerome Cattin-Ortolà , Irini Topalidou, Zivanov, J., Nakane, T., Forsberg, B.O., Kimanius, D., Hagen, W.J., Lindahl, E., and Scheres, S.H. (2018). New tools for automated high-resolution cryo-EM structure determination in RELION-3.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are grateful to Thomas Hinds and Ning Zheng for assistance with the crystallization robot and BLI device; to Jerome Cattin-Ortolà , Irini Topalidou, Zivanov, J., Nakane, T., Forsberg, B.O., Kimanius, D., Hagen, W.J., Lindahl, E., and Scheres, S.H. (2018). New tools for automated high-resolution cryo-EM structure determination in RELION-3.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Studies of the S glycoproteins of MERS-CoV and the bat-specific HKU4 coronavirus suggested that glycans also impact zoonosis by modulating cleavage-site accessibility to proteases for membrane-fusion activation (Yang et al, 2015). The outcome of the arms race between viral evolution mechanisms and the immune system of infected individuals can also lead to the elicitation of antibodies binding glycan-containing epitopes, such as in the case of HIV-1 (Scharf et al, 2015;Stewart-Jones et al, 2016) or Epstein-Barr virus (Snijder et al, 2018). These findings emphasize the necessity to obtain a detailed understanding of the carbohydrates covering coronavirus S glycoproteins to accelerate the development of subunit vaccines and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Methods have recently been developed to further improve the sensitivity for detecting rare antigen-specific B cells. Magnetic nanoparticles conjugated to antibodies targeting the fluorochrome on the antigen of interest, allow for the enrichment of antigen-specific B cells prior to flow cytometry (20,26,80,83). This approach is particularly useful for detecting rare antigenspecific naïve B cells, autoreactive B cells, memory B cells, and plasmablasts (21,26,47,50).…”
Section: Methods For Rare Antigen-specific B Cellsmentioning
confidence: 99%
“…Like RSV, HIV, and influenza, the fusion proteins of EBV and CMV exist in a pre-fusion conformation, and stabilization in their pre-fusion states could greatly accelerate vaccine development against these pathogens (17)(18)(19). Rare memory B cells producing antibodies specific for the EBV fusion machinery have been isolated; these can neutralize both B cell and epithelial cell infection (20). A new paradigm in malaria vaccine development is also emerging with the discovery of IgM+ and IgD+ memory B cells targeting the Merozoite Surface Protein 1, that rapidly respond to malaria re-infection (21).…”
Section: Why Study B Cell Responses? Opportunities For Applying Technmentioning
confidence: 99%
“…Glycoproteins from Ebola virus were modified by removing the mucin-like domain, assembled as soluble trimers, and then studied in a complex with the ADI-15878 Fab by SPA (Murin et al 2018). Except for the above-mentioned trimeric forms, glycoprotein complexes containing more than one viral glycoprotein (e.g., gH/gL/gp42 from Epstein-Barr virus) have also been used for cryo-EM antibody-antigen studies (Snijder et al 2018). Cryo-EM structures of glycoprotein-antibody complexes are usually captured in intermediate states.…”
Section: Enveloped Viruses Without Icosahedral Symmetrymentioning
confidence: 99%